PENGARUH JUMLAH WAJIB PAJAK, KEPATUHAN WAJIB PAJAK, TERHADAP PENERIMAAN PAJAK PENGHASILAN BADAN DENGAN PEMERIKSAAN PAJAK SEBAGAI VARIABEL MODERASI PADA KANTOR PELAYANAN PAJAK PRATAMA SALATIGA (Students' Journal of Accounting and Banking, 2015)
This study aims to identify and analyze the influence of the number of taxpayers, tax compliance, the corporate income tax revenue with tax audits as a moderating variable in the Tax Office Primary Salatiga. This study uses quantitative data using secondary data obtained from STO Salatiga. The sample used in this study is on the period January 2011 to December 2013 Analysis of the data used in this study is the use of multiple linear regression analysis. The results of this study stated that the number of taxpayers have no effect and a negative result to tax revenues, while tax compliance, positive and significant impact on the corporate income tax revenue with tax audits as a moderating variable in the Tax Office Primary Salatiga.Keywords: Taxpayer Number, Taxpayer Compliance, Tax Audit, Tax Receipts Article 25/29, KPP Pratama Salatiga, 2014